Validity and reliability of the religious belief instrument - Norsaleha Mohd. Salleh,; Ab. Halim Tamuri,; Salleh Amat, (Universiti Kebangsaan Malaysia, 2013)
This article discussed the construct validity and reliability of faith appreciation questionnaire. The instrument was developed based on past literature, expert opinion and research objectives. Expert interview has been done to validate the instrument construct and content while Cronbach’s alpha coefficient has been used to identify the value and level of internal consistency. Result shows the overall value of Cronbach’s alpha for the instrument is 0.868. However, each construct show a different value of reliability such as moderate level in understanding, α = 0.662; very high value of feeling, α = 0.910 and high in practicing, α = 0.830. Based on the result, some improvements on the instrument item need to be done for the next research.